ANALISIS PLS-SEM TERHADAP KESIAPAN DIGITAL ORANG TUA SISWA SMAN 2 KABANJAHE DALAM MENGHADAPI ERA INDUSTRI 4.0 - br Tarigan, Anastasya Primsa; br Tarigan, Enita Dewi; Zahedi, Zahedi; Gio, Prana Ugiana (MES: Journal of Mathematics Education and Science, 2025)
The Fourth Industrial Revolution has significantly transformed various aspects of life, including education. The rapid advancement of digital technology requires society, including parents, to adapt, particularly with the implementation of online school enrollment systems. However, this situation creates challenges for parents unfamiliar with technology, leading to a digital divide. This study examines the factors influencing parents’ digital readiness at SMAN 2 Kabanjahe using the Technology Readiness Index (TRI), which evaluates individual attitudes toward technology through four dimensions: optimism, innovativeness, discomfort, and insecurity. A quantitative approach was employed with data collected from 80 parents via online questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) in Smart-PLS 4.0. The results show an R² value of 0.615, indicating that 61.5% of the variance in digital readiness is explained by the model. Optimism has a significant positive effect, while discomfort has a significant negative effect. Conversely, innovativeness and insecurity do not significantly influence digital readiness. These findings highlight the applicability of the TRI model in assessing digital readiness, particularly in the educational context.